Tradition: A Critical Primer - Engler, Steven (Equinox Publishing, 2024)
This book looks at the concept of tradition in the study of religion. It examines the history of the concept, uses in the discipline, theoretical perspectives (including Indigenous and post/decolonial studies, cognitive science and hermeneutics), and critical perspectives on key thinkers (Halbwachs, Gadamer, Ricoeur, J & A Assmann, Boyer, Morin) and recommendations for clearing the air of a key theoretical tension surrounding the concept of the invention of tradition. Questioning the use of 'tradition' as a synonym for 'religion,' the book models a relational and ideology-critical approach to complex concepts. It engages with important theoretical issues, including opposition to 'modernity,' Indigenous 'self-conscious traditionalism.' colonial discourses, intersections with ritual, agency and reason and 'the invention of tradition.' Discussions - with examples from a variety of religions and cultures - including African, Indigenous North American, south Pacific, Afro Brazilian, Japanese, Jewish, Christian, Muslim, Buddhist, Hindu and esoteric. Four case studies - on esoteric Traditionalism, Candomble, great/little traditions and Indigenous traditions in Canadian law - engage central ideas in greater detai